Titanium carbide nanosheets with defect structure for photothermal-enhanced sonodynamic therapy - Guangqiang Li (KeAi Communications Co., Ltd., 2022)
Sonodynamic therapy (SDT) has attracted widespread interest in biomedicine, owing to its novel and noninvasive therapeutic method triggered by ultrasound (US). Herein, the Ti3C2 MXene nanosheets (Ti3C2 NSs) are developed as good sonosensitizers via a two-step method of chemical exfoliation and high-temperature treatment. With the high-temperature treatment, the oxygen defect of Ti3C2 MXene nanosheets (H–Ti3C2 NSs) is greatly increased. Therefore, the electron (e−) and hole (h+) generated by US can be separated faster due to the improved degree of oxidation, and then the recombination of e−-h+ can be prevented with the abundant oxygen defect under US irradiation, which induced the sonodynamic efficiency greatly to improve around 3.7-fold compared with Ti3C2 NSs without high-temperature treatment. After PEGylation, the H–Ti3C2-PEG NSs show good stability and biocompatibility. In vitro studies exhibit that the inherent property of mild photothermal effect can promote the endocytosis of H–Ti3C2-PEG NSs, which can improve the SDT efficacy. In vivo studies further display that the increased blood supply by the mild photothermal effect can significantly relieve hypoxia in the tumor microenvironment, showing photothermal therapy (PTT) enhanced SDT. Most importantly, the H–Ti3C2-PEG NSs can be biodegraded and excreted out of the body, showing no significant long-term toxicity. Our work develops the defective H–Ti3C2 NSs as high-efficiency and safe sonosensitizers for photothermal-enhanced SDT of cancer, extending the biomedical application of MXene-based nanoplatforms.